The effect of resistance exercises performed at home on swimming performance of adolescent swimmers during the covid-19 pandemic period - Umay, B.; Atar, Ö.; Koç, H. (VIREF Revista De Educación Física, 2022)
Aim: to examine the effect of resistance exercises performed at home on swimming performance in adolescent swimmers during the COVID-19 pandemic period.